Critical thinking skills and science process skills in physics practicum. Issue 1 (March 2021) - Firmansyah, J; Suhandi, A
Abstract: The purpose of this article is to analyze the differences between indicators of science process skills and critical thinking skills in physics practicum. Both of these skills have the same indicators but certainly have differences. How to distinguish definitions and measurements of science process skills and critical thinking skills that are interrelated such as interpretation, inferring and predicting. These three indicators have different meanings in aspects of science process skills and critical thinking skills. The research method used is a literature review with descriptive analysis. The data used in this study are secondary in the form of articles, reports and books relating to science process skills and critical thinking skills in physics practicum. The data collection method used in this study is the documentation method. The analysis shows that the three intersecting indicators have different definitions and measurements. Therefore, in physics practicum, science process skills and critical thinking skills must be measured with different instruments and with different treatments. Critical thinking skills emerge after mastering content and concepts well and comprehensively, while science process skills are trained through the process to obtain physical concepts and content.